Książę Radziwiłł Karol Stanisław "Panie Kochanku" w twórczości Zygmunta Krasińskiego i innych romantyków. Dylematy edytora i historyka literatury = Prince Karol Stanisław Radziwiłł "Panie Kochanku" in romantics' writings by Zygmunt Krasiński and other romantics. Dilemmas of an editor and a historian of literature - Kulczycka, Dorota (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The content of the study concerns the presence of Karol Stanisław Radziwiłł ?Panie Kochanku? motive in Polish romantic literature especially in the works by Zygmunt Krasiński. The authoress describes the issues of his story ["Panie Kochanku. Story" - "Panie Kochanku. Powiastka"] and considers their editorial and artistic values, moreover searches alleged sources of a young poet's (Krasiński) knowledge about the eccentric magnate. She also ponders if Krasiński might have known the story from Mickiewicz - a friend to Henryk Rzewuski who was retelling chats about both Radziwiłł and his indispensable companion Włodkowic. The other thread of the article concentrates on reflections regarding Mickiewicz and his opinions on the two erstwhile Sarmatians.
Keywords: Mickiewicz, Adam (1798-1855); Krasiński, Zygmunt (1812-1859); Rzewuski, Henryk (1791-1866); edytorstwo; prawda historyczna; fikcja literacka; "Panie Kochanku"; editorship; historical thrut; literary fiction